Immunological Techniques to Assess Protein Thiol Redox State: Opportunities, Challenges and Solutions - James Nathan Cobley; Holger Husi (MDPI AG, 2020)
To understand oxidative stress, antioxidant defense, and redox signaling in health and disease it is essential to assess protein thiol redox state. Protein thiol redox state is seldom assessed immunologically because of the inability to distinguish reduced and reversibly oxidized thiols by Western blotting. An underappreciated opportunity exists to use Click PEGylation to realize the transformative power of simple, time and cost-efficient immunological techniques. Click PEGylation harnesses selective, bio-orthogonal Click chemistry to separate reduced and reversibly oxidized thiols by selectively ligating a low molecular weight polyethylene glycol moiety to the redox state of interest. The resultant ability to disambiguate reduced and reversibly oxidized species by Western blotting enables Click PEGylation to assess protein thiol redox state. In the present review, to enable investigators to effectively harness immunological techniques to assess protein thiol redox state we critique the chemistry, promise and challenges of Click PEGylation.